Generation and Use of Recombinant Galectins. Issue 3 (3rd March 2021) - Wu, Shang‐Chuen; Paul, Anu; Ho, Alex; Patel, Kashyap R.; Allen, Jerry William Lynn; Verkerke, Hans; Arthur, Connie M.; Stowell, Sean R.
Abstract: Galectins are soluble carbohydrate binding proteins that can bind β‐galactose‐containing glycoconjugates by means of a conserved carbohydrate recognition domain (CRD). In mammalian systems, galectins have been shown to mediate very important roles in innate and adaptive immunity as well as facilitating host‐pathogen relationships. Many of these studies have relied on purified recombinant galectins to uncover key features of galectin biology. A major limitation to this approach is that certain recombinant galectins purified using standard protocols are easily susceptible to loss of glycan‐binding activity. As a result, biochemical studies that employ recombinant galectins can be misleading if the overall activity of a galectin remains unknown in a given assay condition. This article examines fundamental considerations when purifying galectins by lactosyl‐sepharose and nickel‐NTA affinity chromatography using human galectin‐4N and ‐7 as examples, respectively. As other approaches are also commonly applied to galectin purification, we also discuss alternative strategies to galectin purification, using human galectin‐1 and ‐9 as examples. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Purification of galectins using lactosyl‐sepharose affinity chromatography Basic Protocol 2 : Purification of human galectin‐7 using a nickel‐NTA affinity chromatography column Alternate Protocol 1 : Iodoacetamide alkylation of free sulfhydryls on galectin‐1 Alternate Protocol 2 : Purification of human galectin‐9 using lactosyl‐sepharose column chromatography